2010
DOI: 10.1007/s10654-010-9493-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, morbidity and mortality in twins: a 24-year prospective follow-up

Abstract: The aim of this study was to find out whether persistent leisure-time physical activity, adjusted for genetic liability and childhood experiences, protect against occurrence of specific chronic diseases and all-cause mortality. Study design was a 24-year prospective follow-up after 6-year physical activity discordance in twin pairs. From 5663 healthy adult twin pairs, 146 pairs (including 29 mozygotic) discordant for both intensity and volume of leisure physical activity at baseline in both 1975 and 1981 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…However, the association between self-reported PA and mortality has previously been evaluated in twin studies with somewhat inconclusive results. In studies based on the Finnish Twin Cohort, lower risk of mortality was observed in twins with higher levels of self-reported PA ( 34 , 35 ). However, the associations were significant only in the subcohort of dizygotic twins, which might indicate residual genetic confounding or lack of statistical power.…”
Section: Discussionmentioning
confidence: 96%
“…However, the association between self-reported PA and mortality has previously been evaluated in twin studies with somewhat inconclusive results. In studies based on the Finnish Twin Cohort, lower risk of mortality was observed in twins with higher levels of self-reported PA ( 34 , 35 ). However, the associations were significant only in the subcohort of dizygotic twins, which might indicate residual genetic confounding or lack of statistical power.…”
Section: Discussionmentioning
confidence: 96%
“…Physical activity during childhood and adolescence seems to play a modest role in adult disease, and this effect seems to be short lasting and disappear after some time [40]. In the Finnish Twin Cohort Study [15], co-twins with less physical activity had increased adult mortality, but the effect was only seen in dizygotic (and not monozygotic) twins, and so the authors could not exclude residual genetic confounding. Longitudinal studies such as the Oslo Youth Study [14], and The Amsterdam Growth and Health Longitudinal Study [41] have found no evidence for a beneficial effect of physical activity during adolescence beyond the age of 40.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of physical activity on mortality has also been shown in several studies, yet there is not enough information about the effects of life-course activity on adult morbidity and mortality [14], especially in low- and middle-income countries. While some investigators have shown long-term effects of physical activity during early life on mortality and health outcomes [15], others believe that this effect fades after the age of 40 [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Grip strength is a signifi cant determinant of functional performance ( 2 ), but good balance reduces the risk of fall-related injuries in older people ( 3 ). Conversely, an inactive lifestyle is linked to an increased risk of death and disability ( 4 ).…”
mentioning
confidence: 99%